On Fertility, Migration, and Remittances in LDCs - Eliakim Katz; Oded Stark (Harvard University, Center for Population Studies, 1985)
In this paper we examine the effect of migratory opportunities for children on fertility when the decision by the child whether and how much to remit is endogenous to the analysis. We differentiate between two classes of motivations to remit and four changes that are likely to increase the return to migration. We demonstrate that the effect of each of these changes on remittances depends on the motive for remittances. Given that the demand for children as assets depends on the returns to them of which remittances constitute a part we identify links between motivations to remit and the demand for children.
Keywords: 330